2021
DOI: 10.3390/agronomy11071386
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Immobilisation and Microbial Biomass Build-Up Induced by Miscanthus x giganteus L. Based Fertilisers

Abstract: Cultivation of Miscanthus x giganteus L. (Mis) with annual harvest of biomass could provide an additional C source for farmers. To test the potential of Mis-C for immobilizing inorganic N from slurry or manure and as a C source for soil organic matter build-up in comparison to wheat (Triticum aestivum L.) straw (WS), a greenhouse experiment was performed. Pot experiments with ryegrass (Lolium perenne L.) were set up to investigate the N dynamics of two organic fertilisers based on Mis at Campus Klein-Altendorf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
(103 reference statements)
1
2
1
Order By: Relevance
“…There, a tendency of a greater N immobilisation after application of fertilisers with Mis biomass (CS-Mis, CM-Mis) compared to WS amended fertilisers were explained by the microbial processes due to the biochemical differences in the carbon/nitrogen (C/N) ratio of the added substrates [33,[59][60][61]. In our field experiment, the differences of N immobilisation between Mis amended and WS amended fertilisers were less obvious compared to those of Stotter et al [34]. The Mis based fertilisers were characterised by a greater C/N ratio of between 25 to 35 for CS-Mis and CM-Mis, compared to a C/N ratio of 11 to 19 for CS-WS and CM-WS (Table 2).…”
Section: Miscanthus As C Source For Microbial N Immobilisationcontrasting
confidence: 64%
See 2 more Smart Citations
“…There, a tendency of a greater N immobilisation after application of fertilisers with Mis biomass (CS-Mis, CM-Mis) compared to WS amended fertilisers were explained by the microbial processes due to the biochemical differences in the carbon/nitrogen (C/N) ratio of the added substrates [33,[59][60][61]. In our field experiment, the differences of N immobilisation between Mis amended and WS amended fertilisers were less obvious compared to those of Stotter et al [34]. The Mis based fertilisers were characterised by a greater C/N ratio of between 25 to 35 for CS-Mis and CM-Mis, compared to a C/N ratio of 11 to 19 for CS-WS and CM-WS (Table 2).…”
Section: Miscanthus As C Source For Microbial N Immobilisationcontrasting
confidence: 64%
“…This field trial showed a tendency of greater N immobilisation and lower inorganic N contents after application of Mis based fertilisers, whereas differences were not significant. In pot experiments, the effectiveness of Mis and WS biomass amended fertilisers for N immobilisation was already detected [34]. There, a tendency of a greater N immobilisation after application of fertilisers with Mis biomass (CS-Mis, CM-Mis) compared to WS amended fertilisers were explained by the microbial processes due to the biochemical differences in the carbon/nitrogen (C/N) ratio of the added substrates [33,[59][60][61].…”
Section: Miscanthus As C Source For Microbial N Immobilisationmentioning
confidence: 98%
See 1 more Smart Citation
“…The finding that greenwaste compost applications slightly increased leaf chlorophyll levels and grain protein content in winter-wheat and did not affect leaf chlorophyll and protein levels in spring-wheat suggests that the high C:N ratio compost did not result in immobilisation/locking-up of N as has been previously reported for organic fertilisers, composts and plant residue inputs with a C:N-ratio of >20 [31][32][33][34].…”
supporting
confidence: 62%